Ethnomedicinal plants traditionally used in treating measles in the Philippines: a review - Angel Mae Frias Luga; Cesar Guinanao Demayo (International Journal of Public Health Science (IJPHS), 2026)
Measles, despite the continuous significant advancements in the field of science, still poses a major health threat worldwide. While vaccines have significantly reduced measles-related morbidity and mortality, access to alternative treatments remains critical for populations unable to receive immunization due to medical, cultural, or socioeconomic barriers. With that, looking into some readily available, cost-effective, and safe alternatives for the treatment of measles is necessary. Given the therapeutic potential of medicinal plants, the main objective of this study is to conduct an ethnobotanical review on the medicinal plants that have been traditionally used in the Philippines for measles treatment. In this review, findings reveal a wide array of plant species that have been traditionally used for measles treatment. A total of 45 medicinal plant species belonging to 25 families were found to have been used in the Philippines to traditionally treat measles. Moreover, data show that Poaceae has the highest number of plant species, which constitutes 11.11% of medicinal plant species in the Philippines, with therapeutic potential against measles. This consolidated data highlights potential low-cost alternatives to conventional therapies and underscores the need for further pharmacological validation of these remedies to enhance their integration into public health strategies.